Integration Tendencies of Iceland into the EU after the Outbreak of the Global Financial Crisis and the Impact of Their Economic Situation on the EU Membership - Hovorková, Katarína, 1992-
Analýza vzťahu Islandu k integrácii do EÚ po vypuknutí globálnej finančnej krízy. Hospodárske ukazovatele Islandu. Mienka Islandu o EÚ a eure.